SIGNIFIKANSI GURU AGAMA BUDDHA VIHARA BUDDHA MANGGALA DALAM MEMPERKOKOH KEYAKINAN UMAT BUDDHA TERHADAP BUDDHADHAMMA - Rangga (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2021)
The importance of a religion teacher in general is an educational task which includes educating, teaching, and training. A teacher is very important to assist students in developing students' skills and knowledge. Therefore, the teacher must be able to make students interested in following the lesson. The importance of a Buddhist teacher in guiding Buddhists to be enthusiastic in participating in the activities at Manggala Buddhist Temple, so for strengthen Buddhist belief in the Buddhadhamma. With increasing belief in Buddhadhamma, people in the village will not change their beliefs. This study aims to determine the influence of a Buddhist teacher in strengthening the beliefs of the people in Manggala Buddhist Temple, Buluh Kuning Village. The method used is a qualitative descriptive, and sets the focus of the research, namely: The Significance of Buddhist Teachers at the Manggala Buddhist Temple in Strengthening Buddhist Beliefs in Buddhadhamma.